Leading change to co-teaching in primary schools: a "Down Under" experience. Issue 4 (8th August 2018) - Mackey, J.; O'Reilly, N.; Jansen, C.; Fletcher, J.
Abstract: Traditional conceptions of teaching are being challenged as many schools, especially in New Zealand and Australia, are designing and implementing multi-class flexible learning environments. These de-privatised, innovative learning spaces provide opportunities for teachers to work differently in collaborative co-teaching teams to collectively address diverse learners' needs. This mixed method study investigates the perspectives of teachers' and principals' experiences of transitioning to a co-teaching environment and highlights some of the emerging opportunities and challenges that leaders face in supporting teachers to work effectively in these collaborative contexts. While leading the transition requires vision and provision of organisational resources, the findings endorsed the need for professional learning and development to equip teachers to work together effectively with a strong focus on improving student outcomes.